2019
DOI: 10.1136/annrheumdis-2019-215763
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun metagenomics reveals an enrichment of potentially cross-reactive bacterial epitopes in ankylosing spondylitis patients, as well as the effects of TNFi therapy upon microbiome composition

Abstract: ObjectivesDiverse evidence including clinical, genetic and microbiome studies support a major role of the gut microbiome in the common immune-mediated arthropathy, ankylosing spondylitis (AS). We set out to (1) further define the key microbial characteristics driving disease, and (2) examine the effects of tumour necrosis factor-inhibitor (TNFi) therapy upon the microbiome.MethodsThe stools from a case–control cohort of 250 Han-Chinese subjects underwent shotgun metagenomic sequencing. All subjects were genoty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 64 publications
8
69
2
2
Order By: Relevance
“…Furthermore, patients with AS have recently been shown to have a different microbiome composition to controls, with evidence of dysbiosis. [78][79][80] It should be noted that different studies using different methodologies have found somewhat differing results, with no single species or genus of bacteria being consistently found enriched (or absent) in all studies. We would hypothesize that AS may be associated with broad change in the microbiota, perhaps leading to altered Type 17 immunogenicity or altered metabolic signalling (see below) or both.…”
Section: The Gut Microbiome and Asmentioning
confidence: 98%
“…Furthermore, patients with AS have recently been shown to have a different microbiome composition to controls, with evidence of dysbiosis. [78][79][80] It should be noted that different studies using different methodologies have found somewhat differing results, with no single species or genus of bacteria being consistently found enriched (or absent) in all studies. We would hypothesize that AS may be associated with broad change in the microbiota, perhaps leading to altered Type 17 immunogenicity or altered metabolic signalling (see below) or both.…”
Section: The Gut Microbiome and Asmentioning
confidence: 98%
“…Taken together, there is substantial evidence supporting the notion that complex interactions between host genetics, environmental factors, and the gut microbiome drive the pathogenesis of SpA [ 146 ]. Pathogenic bacteria, and possibly viruses occurring in the gut of SpA patients, contribute to dysbiosis, and lead to immune dysfunction and modulation of the innate and adaptive immune responses ([ 126 ].…”
Section: Models Of Spa Pathogenesis: Hypothesesmentioning
confidence: 99%
“…Type IV hypersensitivity is mediated by CD4+ type 1 helper T cells (Th1) and CD8+ cytotoxic T cells, and it is classified as a delayed-type hypersensitivity since the response requires more than 12 hours after exposure to antigens. There have been increasing efforts for identifying cross-reactive T-cell epitopes of pathogens that can initiate type IV hypersensitivity reactions and contribute to the pathogenesis of autoimmune diseases via activation of autoreactive CD8+ cytotoxic T cells (Luo et al, 2018b; Venigalla et al, 2020; Whalley et al, 2020; Yin et al, 2020).…”
Section: Resultsmentioning
confidence: 99%